Jaminan Pelaksanaan Eksekusi Putusan Anak - Fauzan, Ahmad (Institut Agama Islam Negeri Metro, 2024)
A problem that arises in practice in the Indonesian justice system is that many alimony decisions in the Religious Courts are not carried out (or in procedural law terms